2011
DOI: 10.1021/nl1042648
|View full text |Cite
|
Sign up to set email alerts
|

Localized States and Resultant Band Bending in Graphene Antidot Superlattices

Abstract: We fabricated dye sensitized graphene antidot superlattices with the purpose of elucidating the role of the localized edge state density. The fluorescence from deposited dye molecules was found to strongly quench as a function of increasing antidot filling fraction, whereas it was enhanced in unpatterned but electrically backgated samples. This contrasting behavior is strongly indicative of a built-in lateral electric field that accounts for fluorescence quenching as well as p-type doping. These findings are o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 41 publications
1
65
0
Order By: Relevance
“…This suggests new ways of enhancing graphene's photoresponsivity. 31 As the nonradiative decay rate only exists in the presence of graphene, we classify its contributions according to the nature of graphene's excitations: longitudinal (charged) and transverse. Longitudinal (l) excitations couple to both in-plane (p ) and out-of-plane (p z ) components of the dipole matrix elements.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests new ways of enhancing graphene's photoresponsivity. 31 As the nonradiative decay rate only exists in the presence of graphene, we classify its contributions according to the nature of graphene's excitations: longitudinal (charged) and transverse. Longitudinal (l) excitations couple to both in-plane (p ) and out-of-plane (p z ) components of the dipole matrix elements.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the influence of magnetic fields on perfectly periodic GALs and isolated antidots has been studied at the level of full atomistic approaches [25], the Dirac approximation [26], or the simple gapped graphene model [27]. Experimental fabrication of GALs involves invasive techniques such as electron beam or block copolymer lithography [28][29][30][31][32][33][34][35][36][37]. A major issue is the deterioration of the graphene sheet quality and the difficulty in maintaining a uniform size and separation of antidots throughout the lattice.…”
Section: Introductionmentioning
confidence: 99%
“…40 GALs have been proposed as a flexible platform for creating a semiconducting material with a band gap which can be tuned by varying the antidot size, shape, or lattice symmetry. 17,[41][42][43] GALs can be fabricated by electron beam lithography, 44,45 by block copolymer lithography 46,47 with hole distances down to 5 nm, and at a larger scale through nanorod photocatalysis 48 and anisotropic etching. 49 To the best of our knowledge, no studies have been reported on the thermal properties of finite GALs.…”
Section: Introductionmentioning
confidence: 99%